Doris Lessing - Thorpe, Michael (Writers and Their Work Series., 1973)
Doris Lessing's first book, The Grass is Singing, was published in 1950 and was immediately recognized as a novel of outstanding promise. Most of her life up to the age of thirty was spent in Rhodesia and her first four novels and collections of stories all have African settings. Since settling in Britain she has shown that she possesses a far wider range of vision, as well as a remarkable versatility of technique. She is a writer of radical opinions,